Implementation of the Learning Method of Playing, Story, Singing (BCM) in Learning Islamic Religious Education - Zainuddin Zainuddin; Ma’arizul Ajillah Aini; Muhammad Hasyim (EDUCATIO: Journal of Education)
Islamic learning aims to guide students to become a generation of devout, berakhalakqul karimah, foster trust in Allah SWT, live in harmony and peace between religious people based on the Qur'an and Hadith.  State Elementary School (SD) 1 Turen is one of the educational institutions in which it also teaches about Islamic Religious Education. The excellent programs at SD Negeri 1 Turen are Extracurriculars to Read and Write the Qur'an, Dance, Drumband, Scouts and others. Islamic Religious Education is an effort made to know, live, understand, and follow the teachings of the Islamic religion. In this study, researchers used play, story and singing (BCM) methods to improve student learning. The method of playing, story and singing is a fun method to do and something entertaining. So that learners are active and easier to understand the material. The class action research model used in this study is the teacher's research model as a researcher and the classroom action research cycle model developed by Kemmis and Taggart. Based on the results of the study cycles 1 and 2 using the application of the play method, stories and singing students are motivated in learning. This can be proven that student scores in cycle 1 have increased on average student scores increased by 60.87% and were proven in cycle 2, where the average student score increased by 86.96%.